Ad-p53 enhances the sensitivity of triple-negative breast cancer MDA-MB-468 cells to the EGFR inhibitor gefitinib - WANG, XINZHAO; SONG, HONGKUAN; YU, QIAN; LIU, QI; WANG, LEILEI; LIU, ZHAOYUN; YU, ZHIYONG (Oncology reports, 2015)
Triple-negative breast cancer (TNBC) accounts for 20% of all molecular subtypes of breast cancer. Neither endocrine nor anti-HER2 molecular targeting treatment yield promising results. At present, epidermal growth factor receptor (EGFR) inhibitor, as a single agent, is unable to obtain encouraging results in the treatment of TNBC, even though most of these tumors overexpress EGFR. In the present study, we used recombinant human p53 adenovirus (Ad-p53) and EGFR inhibitor gefitinib to treat the TNBC cell line MDA-MB-468. The combined treatment of gefitinib and Ad-p53 synergistically inhibited the proliferation of MDA-MB-468 cells; it restrained colony formation, enhanced cellular apoptosis and arrested the cell cycle in vitro, and decreased tumor burden of xenografts in nude mice. Western blot analysis revealed that Ad-p53 and gefitinib in combination significantly downregulated the phosphorylation of protein kinase B (p-Akt) and upregulated caspase-9 and cleaved caspase-3, while there were minimal effects on the expression of extracellular signal-regulated kinase (ERK) and phosphorylation of ERK (p-ERK). These results suggest that Ad-p53 may block the PI3K/Akt pathway rather than the Raf/MEK/ERK pathway. Importantly, wild-type p53 was able to reverse the drug resistance of MDA-MB-468 cells to gefitinib through inactivation of the phosphatidylinositol 3-kinase (PI3K)/Akt pathway. The apoptotic activity induced by this combined treatment may be regulated by caspase cascade-dependent activation.